Endoscopic Stenting and Clipping for Anastomotic Stricture and Persistent Tracheoesophageal Fistula after Surgical Repair of Esophageal Atresia in an Infant - Mohammed Amine Benatta; Amine Benaired; Ahmed Khelifaoui (Case Reports in Medicine)
Anastomotic stricture (AS) and recurrent tracheoesophageal fistula (TEF) are two complications of surgical repair of esophageal atresia (EA). Therapeutic endoscopic modalities include stenting, tissue glue, and clipping for TEF and endoscopic balloon dilation bougienage and stenting for esophageal strictures. We report herein a two-month infant with both EA and TEF who benefited from a surgical repair for EA, at the third day of life. Two months later he experienced deglutition disorders and recurrent chest infections. The esophagogram showed an AS and a TEF confirmed with blue methylene test at bronchoscopy. A partially covered self-expanding metal type biliary was endoscopically placed. Ten weeks later the stent was removed. This allows for easy passage of the endoscope in the gastric cavity but a persistent recurrent fistula was noted. Instillation of contrast demonstrated a fully dilated stricture but with a persistent TEF. Then we proceeded to placement of several endoclips at the fistula site. The esophagogram confirmed the TEF was obliterated. At 12 months of follow-up, he was asymptomatic. Stenting was effective to alleviate the stricture but failed to treat the TEF. At our knowledge this is the second case of successful use of endoclips placement to obliterate recurrent TEF after surgical repair of EA in children.